2007
DOI: 10.1093/jxb/erm033
|View full text |Cite
|
Sign up to set email alerts
|

Comparing nitrate storage and remobilization in two rice cultivars that differ in their nitrogen use efficiency

Abstract: Soil nitrogen (N) is available to rice crops as either nitrate or ammonium, but only nitrate can be accrued in cells and so factors that influence its storage and remobilization are important for N use efficiency (NUE). The hypothesis that the ability of rice crops to remobilize N storage pools is an indicator of NUE was tested. When two commonly grown Chinese rice cultivars, Nong Ken (NK) and Yang Dao (YD), were compared in soil and hydroponics, YD had significantly greater NUE for biomass production. The abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 34 publications
7
57
0
6
Order By: Relevance
“…NR activity was measured by the modified method of Fan et al (2007). Fresh samples (0.5 g) were frozen in liquid N 2 , ground into powder in the presence of acid-washed sand and homogenized with 4 mL of extraction buffer (0.025mol L -1 phosphate buffer, pH 8.7, 1.211g L 21 Cys, 0.372g L 21 EDTA).…”
Section: Nr and Gs Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…NR activity was measured by the modified method of Fan et al (2007). Fresh samples (0.5 g) were frozen in liquid N 2 , ground into powder in the presence of acid-washed sand and homogenized with 4 mL of extraction buffer (0.025mol L -1 phosphate buffer, pH 8.7, 1.211g L 21 Cys, 0.372g L 21 EDTA).…”
Section: Nr and Gs Activitiesmentioning
confidence: 99%
“…Fresh samples (0.5 g) were frozen in liquid N 2 , ground into powder in the presence of acid-washed sand and homogenized with 4 mL of extraction buffer (0.025mol L -1 phosphate buffer, pH 8.7, 1.211g L 21 Cys, 0.372g L 21 EDTA). Homogenates were centrifuged at 30,000 g for 15 min at 4°C, and the supernatants were treated with sulfanilamide and a-naphthylamine reagents for colorimetric (540 nm) determination of nitrite as described by Fan et al (2007).…”
Section: Nr and Gs Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that once taken up, NO 3 in the vegetative stage could contribute to the photosynthesis of the following growth stage. Recently, some supporting results for this phenomenon have been reported by Fan et al (2007). They measured leaf nitrate reductase activity (NRA) by nitrate withdrawal from the culture solution by using rice varieties with different NUE.…”
Section: Effect Of Nitrate Supply During the Vegetative Stagementioning
confidence: 73%
“…Varietal differences exist in NO 3 uptake (Luo et al 1993;Yang et al 1999;Duan et al 2006Duan et al , 2007aDuan et al , 2007bFan et al 2007;Senoo et al 2007). Similarly, there is a varietal difference in NRA, e.g., indica has higher activity than japonica (Barlaan and Ichii 1996).…”
mentioning
confidence: 99%